A Simple and Robust Approach for Evaluation of Antivirals Using a Recombinant Influenza Virus Expressing Gaussia Luciferase - Li, Ping (Viruses, 2018)
Influenza A virus (IAV) causes seasonal epidemics and occasional but devastating pandemics, which are major public health concerns. Because the effectiveness of seasonal vaccines is highly variable and the currently available drugs are limited in their efficacy because of the emergence of drug resistance, there is an urgent need to develop novel antivirals. In this study, we characterized a recombinant IAV-carrying Gaussia luciferase (Gluc) gene and determined its potential as a tool for evaluating therapeutics. We demonstrated that this recombinant IAV is replication-competent in tissue culture and pathogenic in mice, although it is slightly attenuated compared to the parental virus. Luciferase expression correlated well with virus propagation both in vitro and in vivo, providing a simple measure for viral replication in tissue culture and in mouse lungs. To demonstrate the utility of this virus, ribavirin and oseltamivir phosphate were used to treat the IAV-infected cells and mice, and we observed the dose-dependent inhibition of viral replication by a luciferase assay. Moreover, the decreased luciferase expression in the infected lungs could predict the protective efficacy of antiviral interventions as early as day 2 post virus challenge. In summary, this study provides a new and quantitative approach to evaluate antivirals against IAV.